Screen time and child development : the effects on children´s social skills and academic performance - Emilía Katrín Böðvarsdóttir 1999- (2021)
With increased media exposure and technological improvements, children´s screen time is rapidly increasing. Research has found associations between screen time and various developmental factors such as academic performance, social skills, physical health, and activity involvement. However, few studies have distinguished between types of screen time and how they relate to these factors. The aim of this study was to research whether total screen time and/or certain types of screen use is associated with academic performance and social skills. The mediating effects of physical activity and extracurricular activity engagement on the relationship between screen time and social skills was tested. The study was cross-sectional and data from The Icelandic Centre for Social Research & Analysis (ICSRA) were used for analysis. One of their questionnaires, Youth in Iceland 2017, was used in this study with a random sample of 2152 children between the ages of 10-12. Linear regression was used for data analysis which showed that both academic performance and social skills were negatively associated with screen time. Physical activity and physical-based extracurricular activity engagement had a significant mediation effect on the relationship between screen time and social skills. Future research should emphasize longitudinal effects of screen time to gather further information about developmental outcomes. Key words: Screen time, academic performance, social skills, physical activity, extracurricular activities Með auknu aðgengi að tækni og miðlum hefur skjátími meðal barna aukist til muna. Rannsóknir hafa fundið tengsl milli skjánotkunar og margvíslegra þroskatengdra þátta, s.s. námsárangurs, félagsfærni, hreyfingar og tómstundaiðkunar. Hinsvegar hafa fáar rannsóknir gert greinamun á áhrifum mismunandi tegunda skjánotkunar á þessa þætti. Markmið rannsóknarinnar var að rannsaka hvort heildarskjátími og/eða ákveðnar tegundir skjánotkunar hafi tengsl við námsárangur og félagsfærni. Miðlunaráhrif hreyfingar og ...